Critical conditions for pit initiation and growth of austenitic stainless steels. (March 2015) - Al Ameri, M.; Yi, Y.; Cho, P.; Al Saadi, S.; Jang, C.; Beeley, P.
Highlights: Metastable and stable pitting behaviour of 316 stainless steel was investigated. Potentiodynamic (PD) and potentiostatic (PS) polarization was used. The initiation of metastable pitting was related to cumulative electric charge. Mode change from PD to PS below pitting potential inhibited stable pit growth. Abstract: The pitting behaviour of 316 stainless steel in NaCl solution was investigated using potentiodynamic (PD) and potentiostatic (PS) polarization. Tests with the mode change from PD to PS at potentials close to the pitting potential showed that the potential could play a role in the stable pitting by maintaining the pit stability product. The metastable pit growth was studied by changing the mode at potentials far below the pitting potential and by characterizing the first current density spikes. The results suggested that the cumulative electric charge density governs the metastable pit initiation as a critical condition.